CYPRODINIL, PYRIMETHANIL, PROPINEB AND TRIFLOXYSTROBIN ON APPLE SCAB CONTROL - BERTON, Onofre; MAY DE MIO, Louise Larissa; SANTOS, Hellen Aparecida Arantes dos (Scientia Agraria, 2007)
Effects of the fungicides cyprodinil, pyrimethanil, propineb and trifloxystrobin were studied for apple scab control on cv “Gala”. Effect of the fungicides was evidenced for systemic compounds and determined by the dose used. On fruits the effect upon apple scab varied between 78% and 100%. On leaves, fungicides controlled apple scab with at least 70% efficiency and none of the fungicides controlled 100%. From December to April the incidence of apple scab disease in the control treatment ranged from 0,0% to 99% reaching severity of 14 lesions/leave. The average number of lesions per leaf in all treatments with fungicides was significantly different from control and the mean control for apple scab was superior to 80%. Neither phytotoxicity over spurs and leaves nor russeting on fruits were observed after ten fungicide sprays.